Poetry from Beyond the Grave - Xavier, Francisco Cândido - Chico (punctum books, 2013)
Poetry from Beyond the Grave is the first English publication of a large selection of poems by the Brazilian medium and Spiritist leader Francisco Cândido "Chico" Xavier. These poems, originally collected in the volume Parnaso de Além-Túmulo, were dictated to Xavier by a variety of spirits of Brazilian poets from the afterlife, as journeying souls or as witnesses of the spiritual city Nosso Lar, "our house." Poetry from Beyond the Grave is a veritable collection of haunted writing, in which poets present their posthumous work as if they were alive. The brilliant translation by Vitor Pequeno is supplemented by an extensive afterword by Jeremy Fernando, who traces what it means to speak through the other.